An Evaluation of Green School Program at SMA Negeri 1 Selong as a Preparation Towards a Swaliba School - Utami, Anggun Dwi (Sumatra Journal of Disaster, Geography and Geography Education, 2018)
This research was aimed to: 1) know the policies applied by the leaders of SMA Negeri 1 Selong (state senior high school 1 Selong) to components of education with respect to the implementation of Green School Program, 2) study students’ and teachers’ activeness and participation in the implementation of Green School Program, 3) study the inhibiting factors of Green School Program implementation, 4) evaluate physical condition of the school according to SWALIBA concept. This qualitative research was set at SMA Negeri 1 Selong in East Lombok Regency. Research population were all residents of SMA Negeri 1 Selong. Before collecting the data, a stratified proportional random sampling was conducted in order to select sample from population. Then, data was obtained through observation, questionnaire, interview and documentation. The result of this research showed that (1) Green School Program had been well implemented according to Adiwiyata guidelines. SWALIBA concept had been practiced and this was evident from curriculum changes that supported management of the environment, integration of environmental materials in school subjects, various environmental action, and the management of eco-friendly facilities by using Green House and Compost House. (2) The school had held some activities that involved students in Adiwiyata Program. School residents also supported Green School Program and it was represented by the level of their participation both in the terms of energy, idea, skill, money and goods. (3) There were no meaningful inhibiting factors because the school could solve them. As a preparation in improving Green School Program to SWALIBA, an evaluation of school physical condition which is in accordance to the concept of SWALIBA was done on environmental indicators. The suitability of environmental indicator variables highly supported the development of SWALIBA concept in SMA Negeri 1 Selong.